Multicentre experience with the frozen elephant trunk technique to treat penetrating aortic ulcers involving the aortic arch - Kreibich, Maximilian; Kremer, Jamila; Vötsch, Andreas; Berger, Tim; Farag, Mina; Winkler, Andreas; Siepe, Matthias; Karck, Matthias; Beyersdorf, Friedhelm; Rylski, Bartosz; Czerny, Martin; Gottardi, Roman (European journal of cardio-thoracic surgery, 2021)
AbstractOBJECTIVES. Our goal was to evaluate the use of the frozen elephant trunk (FET) technique for the treatment of penetrating aortic ulcers involving the a